Faktor Risiko yang Berhubungan dengan Kejadian Stunting pada Anak Balita di Kelurahan Alak Kecamatan Alak Kota Kupang - Angela Albertin Siki; Daniela L. A Boeky; Deviarbi Sakke Tira (Yayasan Literasi Sains Indonesia, 2024)
Stunting is a condition in which a person's height is less than normal based on age and gender. Height is a type of anthropometric examination and shows a person's nutritional status. The presence of stunting indicates a poor nutritional status Malnutrition in the long term (chronic). This study aims to determine the risk factors associated with stunting incidents in children under five years old in alak village, alak sub district, kupang city in 2023. The type of research used is quantitative research using observational analytic methods with a case control research design. The population used for this study was 520 toddlers in Alak Village, Alak District, Kupang City. A sample of 33 cases and 33 controls using simple random sampling technique. Data were taken directly at the research site using a questionnaire and then processed and analyzed using the chi-square test. The results showed that there was a relationship between income level (p=0.001), education level (p=0.004), history of infectious disease (p=0.001), history of exclusive breastfeeding (p=0.044), and birth spacing (p=0.077) with the incidence of stunting in children under five in Alak Village, Alak District, Kupang City. It is hoped that health workers can increase routine monitoring of additional feeding and provide education regarding stunting.